Implementation Of Customer Relationship Management In Order To Build Customer Satisfaction And Loyalty - Salma Fauziyyah; khanifatul khusna (Jurnal Manajemen Indonesia, 2022)
This study aims to examine the impact of the implementation of customer relationship management (CRM) on customer satisfaction and loyalty, and the impact of satisfaction on customer loyalty of government commercial banks (BNI, BRI, Bank Mandiri, and BTN) in East Java Province. The research instrument used was a questionnaire. The research covered employees, technology, sales, products, and performance. The population of this study is all depositors of government commercial banks (BNI, BRI, Bank Mandiri, and BTN) in East Java Province. The sampling method uses purposive sampling with a total sample of 120 respondents taken in three locations in three cities in the East Java region, namely: Jember City represents a small town, Malang City represents a medium city, and Surabaya City represents a large city. The allocation of the number of samples for each bank and each city is carried out proportionally. Data analysis models use Structural Equation Modelling (SEM). The analysis shows that CRM has a significant positive effect on customer satisfaction and loyalty, and customer satisfaction has a significant positive effect on customer loyalty. Keywords — customer relationship management, customer satisfaction, customer loyalty